Essential Oils of Etlingera acanthodes A.D. Poulsen, An Endemic Ginger from Sulawesi Island - Hurria Hurria; Anggra Alfian; Muhammad Fajri Ramadhan Muslim Saleh; Heder Djamaludin; Murni Mursyid; Witno Witno; Asri Subkhan Mahulette (Journal of Tropical Biodiversity and Biotechnology, 2023)
Etlingera acanthodes A.D. Poulsen is a ginger endemic to Sulawesi, and there is no research on its essential oils. The Essential oil information of E. acanthodes is the first reported and has a high novelty. The objective of the study is to analyze the component of E. acanthodes essential oils, which are endemic to Sulawesi. The essential oils obtained by hydrodistillation of the leaves, stems, flowers, and rhizomes of E. acanthodes A.D. Poulsen. The samples were analyzed by GC-MS method using the Agilent Technologies 7890 Gas Chromatograph with Auto Sampler. Data analysis of essential oils of GC-MS results were determined based on comparing mass spectra from the NIST 2005 v.2.0 library and Wiley 7 library 2003. The oils of E. acanthodes contain terpenoids, phenolic, steroids, and other compounds. Phenolic compounds (39.56%) predominate in leaves, other compounds (41.25%) on stems, diterpenes hydrocarbons (77.3%) in flowers, and other compounds (43.5%) and steroids (40.4%) on rhizomes. The five main compounds of E. acanthodes are Neophytadiene; (+)-De-O-Methylcentrolobine; Cholest-5-En-3-Ol,23-Ethyl-,(3. Beta.23S)-; 9,12-Octadecadienoic Acid, Phenol, 2-ethyl-. The analysis found several compounds that can be used for industry and medicine in the future.